2000
DOI: 10.1111/j.1530-0277.2000.tb02072.x
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Concurrent Substance Use Disorders: A Developmental, Typological Approach to Comorbidity

Abstract: Characterizations of alcohol use disorders typically fail to consider important sources of heterogeneity such as course or comorbidity. By simultaneously modeling developmental course and comorbidity with tobacco dependence, we were able to identify distinct trajectories of single and concurrent substance use disorders. Such multi-substance trajectories represent meaningful subtypes that, although sharing substantial common influences, have unique etiologic correlates. Additionally, these subtypes might repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(53 citation statements)
references
References 87 publications
4
49
0
Order By: Relevance
“…Life‐time drinking histories showed that ALD and non‐ALD subjects had different drinking trajectories, with ALD exhibiting significant differences in both drinks per day and drinking days each week by their early 20s. Previous studies of drinking trajectories in young drinkers have identified up to six different patterns [18–22]. Data on levels of alcohol dependency essentially confirms the findings of a previous study from our unit [23], and those of an earlier study from the King's Liver Unit [24], that only a minority of patients with cirrhosis or progressive cirrhosis have evidence of severe alcohol dependency and many have no evidence of dependency at all—they are controlled heavy social drinkers.…”
Section: Resultssupporting
confidence: 83%
“…Life‐time drinking histories showed that ALD and non‐ALD subjects had different drinking trajectories, with ALD exhibiting significant differences in both drinks per day and drinking days each week by their early 20s. Previous studies of drinking trajectories in young drinkers have identified up to six different patterns [18–22]. Data on levels of alcohol dependency essentially confirms the findings of a previous study from our unit [23], and those of an earlier study from the King's Liver Unit [24], that only a minority of patients with cirrhosis or progressive cirrhosis have evidence of severe alcohol dependency and many have no evidence of dependency at all—they are controlled heavy social drinkers.…”
Section: Resultssupporting
confidence: 83%
“…Previous trajectory analysis with US samples has shown decrease in heavier and problematic drinking at about 21 years (Schulenberg et al . 1996; Jackson et al . 2000) but has also identified trajectories of increased binge drinking from ages 18–24 (Schulenberg et al .…”
Section: Discussionmentioning
confidence: 99%
“…Insofar research has focused on individual factors in explaining adolescents’ substance use, most studies have focused on early pubertal timing—mostly in girls (Richards and Oinonen 2011; Stattin et al 2011). Whereas the role of personality in alcohol, tobacco, and marijuana use has been well-established among already using groups (e.g., Chassin et al 2002; Colder et al 2002; Flory et al 2002; Jackson et al 2000; Loukas et al 2000; Otten et al 2008), relatively little research effort has gone into the examination of personality characteristics that might play a role in the onset of substance use in adolescence.…”
Section: Introductionmentioning
confidence: 99%